Unidade de ensino potencialmente significativa (UEPS) para estudo das ligações químicas utilizando smartphones - (:unkn) unknown (Universidade Federal do Pampa, 2019)
This present work started from understanding that student’s access to smartphones offer up opportunities to insert them into education situations, and it is not viable to stop that inclusion. These devices, through app’s installation, acquire different functionalities, making possible their use about a variety of activities. The apps are potential educative materials that make viable the mobile learning. This pedagogical intervention target was to evaluate if a development and usability of a Potential Meaningful Educative Unit, able to teach chemical connection contents, with smartphone’s using, would to contribute to approving studies, surprising the students and ensure them for the class contents, guiding them to build their learning approaches. The choice of this topic was due to its relevance to the teaching of chemistry, since it is learning this subject that the students will have a foundation for understanding the formation and behavior of the chemical substances. Starting from contextualized classes, they will understand the role of chemistry in today's society. This study was develop under David Ausubel’s Significant Learning Theory, aiming to evaluate a Potentially Significant Teaching Unit, created to develop meaningful learnings in the participating students. The application was carry out in an elementary public school’s class of 9th grade, in Bage (RS) Brazilian city. The proposal began with a survey of students' previous knowledge, followed by the presentation of the content in a general way, after what each subject was elaborate in a specific way, objecting progressive differentiation and integrative reconciliation. The obtained analysis from the results provided indications of significant learning, which is the purpose of the Potentially Significant Teaching Unit. It is concluded that the device, only by itself, does not guarantee learning, it must be used in a perspective that takes into account student’s motivation to learn, their previous knowledge; also the didactic materials produced must be potentially significant.
Keywords: Unidade de ensino potencialmente significativa; UEPS; Aprendizagem significativa; Ligações químicas; Mobile learning; Potentially significant teaching unit; PSTU; Meaningful learning; Chemical bonds; CNPQ::CIENCIAS SOCIAIS APLICADAS